2012
DOI: 10.1186/1472-6882-12-126
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neurexan on the pattern of EEG frequencies in rats

Abstract: BackgroundVarious medications of natural origin have effectively treated stress-related disorders, such as sleep disturbances and agitated conditions. The efficacy of Neurexan, a multicomponent, low-dose medication, has been demonstrated in observational studies, but its exact mechanism of action has not been determined.MethodsTo characterize the effects of Neurexan on the central nervous system, we analyzed the spectral frequencies of field potentials in four rat brain areas after a single oral administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…It is approved by the German Federal Institute for Drugs and Medical Devices (German: Bundesinstitut für Arzneimittel und Medizinprodukte [BfArM]) for the treatment of sleep disorders and restlessness. Its effects have been demonstrated in several human ( Doering et al, 2016 , Herrmann et al, 2020 , Hübner et al, 2009H , Waldschütz and Klein, 2008 ) and rodent studies ( Dimpfel, et al, 2012 ). Thus, the intake of Nx4 for 28 days was shown to improve sleep quality by increasing sleep duration and reducing sleep latency as reported in patients’ sleep diaries over 14 days, and at the end of the study ( Waldschütz and Klein, 2008 ).…”
Section: Introductionmentioning
confidence: 97%
“…It is approved by the German Federal Institute for Drugs and Medical Devices (German: Bundesinstitut für Arzneimittel und Medizinprodukte [BfArM]) for the treatment of sleep disorders and restlessness. Its effects have been demonstrated in several human ( Doering et al, 2016 , Herrmann et al, 2020 , Hübner et al, 2009H , Waldschütz and Klein, 2008 ) and rodent studies ( Dimpfel, et al, 2012 ). Thus, the intake of Nx4 for 28 days was shown to improve sleep quality by increasing sleep duration and reducing sleep latency as reported in patients’ sleep diaries over 14 days, and at the end of the study ( Waldschütz and Klein, 2008 ).…”
Section: Introductionmentioning
confidence: 97%
“…Local field potentials induced by standard stimulants in major brain areas, including the striatum of rats, have been analyzed and expressed as electropharmacograms to predict the efficacy and possible mechanisms of action of bioactive substances (Dimpfel, 2009). Changes in the EEG frequency patterns in rats were detected in response to the administration of multicomponent drugs (Dimpfel et al, 2012). Presentation of EEG frequencies following CNS drug administration is sometimes called EEG finger print.…”
Section: Discussionmentioning
confidence: 99%
“…An observational study conducted in 49 German general practices also showed a significantly greater reduction of nervousness/restlessness in participants taking Nx4 (reduction of 11.5 ± 7.3 score units) for two weeks in customized doses than participants taking valerian (reduction of 9.0 ± 6.6 score units) for two weeks (p < 0.001) 22 . Nx4 was also shown to significantly (p < 0.001) change EEG signatures in rats that received a single oral dose of Nx4 in comparison to a vehicle control 23 . Dimpfel et al found altered delta-and theta-waves in the frontal cortex and reticular formation, suggesting a calming effect of Nx4 23 .…”
mentioning
confidence: 90%
“…Nx4 was also shown to significantly (p < 0.001) change EEG signatures in rats that received a single oral dose of Nx4 in comparison to a vehicle control 23 . Dimpfel et al found altered delta-and theta-waves in the frontal cortex and reticular formation, suggesting a calming effect of Nx4 23 . The efficacy of Nx4 on psychological and neuroendocrine responses under acute stress was recently investigated by Doering et al 24 .…”
mentioning
confidence: 90%